2020
DOI: 10.1177/1535759720955167
|View full text |Cite
|
Sign up to set email alerts
|

The Nose Knows: Intranasal Midazolam To Treat Acute Seizures During Inpatient Epilepsy Monitoring

Abstract: [Box: see text]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…In both, the RCTs’ treatment success consisted of two components: First is the seizure termination, and second, there was no seizure remission for up to six hours. Presently, we could not find the categorized percentage of effectiveness of MDZ-NS in different kinds of seizures, but studies by Vossler [ 24 ] and Brigo et al [ 25 ] suggested that midazolam is effective in all kinds of seizures [ 24 , 25 ]. Also, the time to the first seizure following treatment is longer with midazolam nasal spray than with a placebo.…”
Section: Reviewmentioning
confidence: 98%
“…In both, the RCTs’ treatment success consisted of two components: First is the seizure termination, and second, there was no seizure remission for up to six hours. Presently, we could not find the categorized percentage of effectiveness of MDZ-NS in different kinds of seizures, but studies by Vossler [ 24 ] and Brigo et al [ 25 ] suggested that midazolam is effective in all kinds of seizures [ 24 , 25 ]. Also, the time to the first seizure following treatment is longer with midazolam nasal spray than with a placebo.…”
Section: Reviewmentioning
confidence: 98%